Electronic Spectral Studies of Some Schiff Base Chelates of Pr(III) and Nd(III) Metal Ions in Terms of Energy and Intensity Parameters - Sharma, Anu; Arora, Atul; Mathur, Kirty; Mathur, R.P. (Asian Journal of Chemistry, 2010)
Six Schiff bases, namely, H2PAA, H2PBA, H2PDB, H2PCA, H2PCV and H2PCT have been synthesized from o-amino phenol with acetyl acetone, benzoyl acetone and dibenzoyl methane, respectively, and pyrrole-2- carboxaldehyde with β-alanine, L-valine and taurine, respectively, by condensation process. Electronic spectral studies of twelve chelates of metal ions, Pr(III) and Nd(III) with these ligands were carried out in different stoichiometric ratios of metal-ligand in solution. The various energy parameters such as Slater-Condon (Fk) Racah (Ek), Lande ( ζ4f) and intensity parameters such as oscillator strength (P), Judd Ofelt parameters (Tλ) have been computed using partial and regression statistical method. The bonding parameter (b1/2) and nephelauxetic ratio (β) have also been evaluated.